How Parents Provide Support for Their Children’s Learning in Mobile ECCE Contexts: Practitioners’ Views - Mofokeng, Mahudi M.; Okeke, Chinedu (Research and Advances in Education, 2025)
Researchers are increasingly interested in the role of early childhood care and education (ECCE) provided in mobile units in South Africa. By utilizing mainly transport vehicles such as trucks, the practitioners facilitate teaching and learning to the most vulnerable children aged birth to five years in remote rural areas. The study’s primary aim was to explore the practitioners’ views on the support parents provide for their children’s learning in a mobile ECCE context to promote quality service delivery. The study was theoretically anchored by Epstein’s overlapping spheres of influence theory. The researchers adopted the interpretive research paradigm combined with the phenomenological research design to make sense of practitioners’ subjectivity. Qualitative data was obtained from semi-structured, in-depth interviews by selecting and engaging twenty conveniently sampled ECCE practitioners. By adhering to the interview guide, the researchers focused on the study’s objectives to elicit rich data. The collected data was analyzed thematically using the Atlas. Ti software. Findings revealed that parents support practitioners through involvement in decision-making processes, regular meeting attendance, and cleaning the mobile units. It was recommended that better parental support and increased stakeholder interest in children’s early learning will result in children’s enhanced early cognitive development for future success.